Efektifitas Edukasi Pencegahan Carpal Tunnel Syndrome (CTS) pada Pembelajaran Daring Mahasiswa Keperawatan : Pemberdayaan Masyarakat - Titih Huriah; Falasifah Ani Yuniarti; Agustina Rahmawati (Jurnal SOLMA, 2023)
Background: The impact of the Covid-19 pandemic has occurred in various sectors, one of which is the education sector. The government's policy to reduce the transmission rate of Covid-19 in the education sector is to implement online learning. A complaint that often occurs in online learning activities is Carpal Tunnel Syndrome (CTS). CTS is a condition where the wrist and fingers feel pain, numbness, or tingling. The purpose of this service is to prevent the occurrence of CTS in nursing students who do online learning. Method: CTS prevention education activities are focused on nursing students from UNISA Yogyakarta Class of 2020 who are participating in full online learning. Community service activities are carried out in 2 meetings via zoom media. The educational material provided is in the form of knowledge related to CTS and assistance in preventing CTS. The instrument used to measure CTS complaints is the CTS-Q (Carpal Tunnel Syndrome Questionnaire). Results: Students who attended the community service meeting totaled 213 people at the first meeting and 78 students at the second meeting. The average pain scale of UNISA Yogyakarta nursing students class of 2020 during the online learning period was still on a mild scale between 2-3, and the biggest complaint was back pain. Screening results show that most students use gadgets 5-8 hours a day. Conclusion: Reduction of complaints of pain in the wrist among students who do online learning after routine CTS exercises with a p value of 0.027.